2017
DOI: 10.2147/rrtm.s105602
|View full text |Cite
|
Sign up to set email alerts
|

Scrub typhus: risks, diagnostic issues, and management challenges

Abstract: Scrub typhus is an acute febrile illness in the “tsutsugamushi triangle”, transmitted by chiggers that can be treated effectively if detected early. Laboratory testing, including molecular and serological assays, is needed for confirming the diagnosis, especially in the absence of the pathognomonic eschar. In this review, factors that play a role in disease occurrence and clinical clues for diagnosis, in addition to risk factors contributing to disease severity, including mortality, are discussed in detail. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 152 publications
1
55
0
Order By: Relevance
“…Scrub typhus is a zoonotic infection that ensues in an acute febrile illness inherent to the ‘tsutsugamushi triangle’ and caused by intracytosolic, gram-negative bacterium Orientia tsutsugamushi (Paris et al 2013 ; Prakash 2017 ). Humans are the fortuitous host of Leptotrombidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Scrub typhus is a zoonotic infection that ensues in an acute febrile illness inherent to the ‘tsutsugamushi triangle’ and caused by intracytosolic, gram-negative bacterium Orientia tsutsugamushi (Paris et al 2013 ; Prakash 2017 ). Humans are the fortuitous host of Leptotrombidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…These malaria positive serum samples were tested for assessing the analytical specificity of scrub typhus IgM ELISA as previous studies have shown cross reactions. 17,18,19 to determine optimal RDT performance with antibody titre in IFA as comparator. 25 The results…”
Section: Discussionmentioning
confidence: 99%
“…Scrub typhus, also called tsutsugamushi disease, is a vector-borne infectious disease primarily endemic to a region called the Asian-Pacific “tsutsugamushi triangle” (South Asia, Southeast Asia, East Asia, the Pacific Islands and Northern Australia) [1, 2], with occasional case reports from Africa, the Middle East, and South America [2, 3]. Accurate incidence data would most likely increase the current estimates of more than two billion people living in scrub typhus-endemic areas and the occurrence of one million cases of the disease annually [35]. Furthermore, the incidence in all known endemic regions has begun to rise over the last decade [68].…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, the illness can progress to the development of interstitial pneumonia, acute respiratory distress syndrome, meningoencephalitis, acute kidney injury, or disseminated intravascular coagulation. The mortality rate varies and can be as high 50% unless patients are treated sufficiently early in the course of illness with liposoluble antibiotics such as doxycycline, tetracycline, azithromycin, or somewhat less-effective chloramphenicol [3, 10, 11]. The presence of eschars is considered pathognomonic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation